Effect of tool geometry in stir zone for hook formation of dissimilar aluminium alloys - Navaneethakannan, Nandakumar (Strojniški vestnik, 2022)
A recently developed solid-state joining technique called “friction stir spot welding” (FSSW) is used to combine metal alloys with low weldability. Significant experimental work for this study is concentrated on the FSSW of AA6063 and AA5083. The study involved fixture setup and welding pattern parameters for the sizes of the material, all of which were done on a milling machine. A cylindrical shoulder with a concave (10°) square pin profile was taken into consideration using various process parameters. The tool material is heat-treated high-carbon steel. The Taguchi L9 orthogonal array is employed for the experimental model. The influence of FSSW factors including spindle speed, time, and depth was studied, along with the relationship between tensile strength, hardness at the contact region, and hook development, which would be a nominal metallurgical pledge established in the welding zone among the interacting sheet plate. The hook structure was found in the area of contact, and thermomechanical effects were seen in the spot-welding area. It has been determined that the influencing variables are spindle speed and plunge depth. As a consequence, it was determined that a tool spindle speed of 1200 rpm, a time of 25 seconds, and a plunge depth of 0.10 mm offer better mechanical properties. The microstructural analysis of welded region was carried out using a scanning electron microscope (SEM).
Keywords: ANOVA; geometrija kavlja; hook geometry; microstructure; mikrostruktura; multipla regresijska analiza; multiple regression; območje mešanja; stir zone; tehnika Taguchi